Hashimoto's disease - the role of factors and diet in the course of the disease - Ilona Gąbka; Weronika Dalmata; Karolina Gendek; Jan Dąbrowski; Anna Kozłowska; Anna Korzeniowska; Natalia Załęska; Aleksandra Ziółkiewicz (Journal of Education, Health and Sport, 2023)
Introduction: Hashimoto's disease is an autoimmune disorder that develops as a result of a pathological reaction of the patient's immune system, which consequently destroys the body's own healthy cells and tissues. Genetic, environmental and immunological factors influence its development. The disease may initially be asymptomatic. The exact aetiology of the disease is unknown. The worldwide incidence is approximately 10-12%.